Tantalum oxide submicro-particles into microporous coating on polyimide possessing antibacterial property and inducing cellular response for orthopedic application. (December 2021) - Asadullah, Syed; Mei, Shiqi; Yang, Kong; Hu, Xinglong; Wang, Fan; Yu, Baoqing; Wu, Zhaoying; Wei, Jie
Abstract: Surface characteristics of the biomaterials have significant effects on response of osteoblast and formation of new bone tissue. In this study, to improve the bio-performance of polyimide (PI) as an implantable material for bone substitute, concentrated sulfuric acid suspension with tantalum (V) oxide (vTO) submicro-particles of 10w% (PIST10) and 15w% (PIST15) was utilized to modify PI surface. After sulfonation, microporous coatings including vTO particles were created on PI (PIST10 and PIST15) while microporous coating without vTO particles was also created on PI (PIS). Results showed that surface roughness, hydrophilicity and protein adsorption of PIST15 was remarkably higher than PIST10 and PIS. Furthermore, after soaking into simulated body fluid (SBF), no apatite mineralization on PIS was found, while PIST15 with high vTO content exhibited better apatite mineralization compared with PIST10. Moreover, PIS showed low antibacterial property, while PIST15 with high vTO content revealed better antibacterial property compared with PIST10. In addition, cellular response (such as adhesion, proliferation and alkaline phosphatase activity) of bone marrow stromal cells (BMSC) of rat to PIST15 was higher than PIST10 and PIS. In conclusion, the microporous coating of PIST15 including vTO submicro-particles possessed good antibacterial property and bioactivity, which significantly promoted the responses of BMSC. Therefore, PIST15 has potential application prospects for bone substitute. Graphical abstract: Image 1 Highlights: Microporous coating was fabricated on PI surface (PIS) by sulfonation reaction. Microporous coatings included tantalum oxide (vTO) submicro-particles (PIST). PIST exhibited optimized surface properties (e.g., roughness and hydrophilicity). PIST induced cellular responses and possessed antibacterial property.